1995
DOI: 10.2337/diacare.18.9.1233
|View full text |Cite
|
Sign up to set email alerts
|

Renal, Metabolic, and Hormonal Responses to Proteins of Different Origin in Normotensive, Nonproteinuric Type I Diabetic Patients

Abstract: A VPD has significantly different renal effects from an APD equal in protein intake in normotensive type I diabetic patients. This could be explained partly by differences in plasma concentrations of amino acids and IGF-I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
60
1
5

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 36 publications
4
60
1
5
Order By: Relevance
“…The statistically significant relationship between intakes of total protein and AER was observed for animal protein, but not for vegetable protein, a finding which supports other evidence of the specially deleterious effect on renal function of animal protein [21,24,27,56]. Since long-term compliance to low-protein diets is often poor [21,22] a modification of protein intake [22,25,27,28,56,57], substituting vegetable protein for protein from animal sources, should be more fully explored as a feasible therapeutic approach which would also reduce total fat and saturated fatty acid consumption.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The statistically significant relationship between intakes of total protein and AER was observed for animal protein, but not for vegetable protein, a finding which supports other evidence of the specially deleterious effect on renal function of animal protein [21,24,27,56]. Since long-term compliance to low-protein diets is often poor [21,22] a modification of protein intake [22,25,27,28,56,57], substituting vegetable protein for protein from animal sources, should be more fully explored as a feasible therapeutic approach which would also reduce total fat and saturated fatty acid consumption.…”
Section: Discussionsupporting
confidence: 76%
“…Since long-term compliance to low-protein diets is often poor [21,22] a modification of protein intake [22,25,27,28,56,57], substituting vegetable protein for protein from animal sources, should be more fully explored as a feasible therapeutic approach which would also reduce total fat and saturated fatty acid consumption. While high protein intakes were a unanimous finding in all EU-RODIAB centres [32] the pattern of food groups providing protein/animal protein may vary considerably across European countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of an effect among participants taking ACE inhibitors/ARBs may be due to the possibility that both MeDi and ACE inhibitors/ARBs could work through overlapping mechanisms such as lowering intraglomerular pressure or by decreasing inflammation. For instance, the amino acid profile associated with an animal protein diet (compared with a vegetable protein diet) has been associated with increased eGFR (44). Therefore, it is possible that the higher vegetable intake of a Mediterranean diet may exert beneficial effects through improved glomerular hemodynamics, which is a similar effect to that of ACEI/ARBs.…”
Section: Discussionmentioning
confidence: 74%
“…The (33) demonstrated that an animal protein diet was associated with higher plasma levels of valine and lysine than a vegetable protein diet, and plasma valine levels were strongly correlated with GFR. Increases in GFR may cause intraglomerular hypertension, which may lead to progressive loss of renal function (7).…”
Section: Discussionmentioning
confidence: 98%